Ultra-Precision Replication Technology for Fabricating Spiral-Structure Metamaterial - Zhang, Weiguo; Zhu, Guodong; Zhu, Xiaoqiang; Du, Chunlei (Frontiers in Physics, 2020)
Spiral-structure metamaterial (SSM) is of great importance, however, there is less methods to fabricate SSM due to the limitations of material particularity and working accuracy. In this paper, a systematic scheme for fabricating SSM is proposed by employing the metal mold making with diamond-based ultra-precision turning technique and moulding replication method. By studying the path planning algorithm of the turning, moulding error law and a technique of how to compensate the error, a solution for SSM is consequently formed. Our experimental results show a satisfying SSM with the surface roughness under 5 nm and the surface shape error under 0.63 percent of the designed wavelength (30 um). Moreover, this SMM element is processed within 10 min, with low cost in materials and process. Based on these advantages, our SSM processing scheme shows a remarkable potential in precise fabricating phase plates and industrialized application of terahertz metamaterial in the future. Key words: Micron/nano-fabrication, Spiral-structure matamaterial, optics, Terahertz optics elements,